Blood Sugar Regulation during Physical Exercise: Review Article - Puspitsari, Dyah Ayu Aprilyana; Nisa, Natasya Aulia Choirun; Firdaus, Muhammad Naufal; Nabila, Annora Shafa; Zaki, Andi Muhammad; Ramadhani, Hanum Wahyu; Dewangga, Mahendra Wahyu (Universitas Muhammadiyah Surakarta, 2023)
One of the causes of diabetes mellitus is physical activity. Management of physical exercise is one of the 5 pillars of diabetes management apart from diet, medication, education and monitoring. The purpose of this study was to determine the effect of diabetic exercise on reducing blood sugar levels in diabetics. This research is a simple review article research. There were 5 articles reviewed. All articles are themed on physical exercise and blood sugar control. All articles conclude that physical exercise can control blood sugar in diabetes mellitus patients.